CONTEMPORARY INDONESIA-THAILAND ART DANCE: TEACHING MODEL FEMALE BASIC DANCE MOVEMENTS BY ANDROID-BASED MEDIA - Srinin, Wathanan; Lamnaokrut, Teerathorn; Riadil, Ikrar Genidal (UPT Pusat Penerbitan LP2MPP ISI Bali, 2022)
This article reveals the findings from the analysis of data for developing a teaching approach of basic Thai Classical Dance based on the Bloom's three-sided learning theory for concept of teaching which consists of cognitive, affective, and psychomotor. The study also implements the concept of Skinner's type R to create the framework for study objectives and exercises of Basic Thai Classical Dance for students of the Department of Dance Education, Yogyakarta State University, Indonesia. The teaching approach of Basic Thai Classical Dance through process implementations on Model of Teaching. The Integration of Indonesia-Thailand Cultures in Female Basic Dance Movement through Android-Based Media on four steps: 1) Background knowledge on the Basic Dance for Women and Thai Culture, 2) Training of the Basic Dance for Women in Thailand, 3) Connecting the cognitive, affective, and psychomotor aspects and 4) Dancing with songs. Implementation of the Indonesian-Thai cultural integration learning model in the Thai Princess Basic Dance Movement through android-based media with applications. Students can gain cultural background knowledge and able to dance to songs in pairs with the basic elements of wiraga, wirasa, and wirana dances as well as in the context of Basic Thai Classical Dance for Women with effectiveness.